HOLISTIC MANAGEMENT OF A 48 YEAR OLD MAN WITH MATURE CATARACT AND GRADE II OBESE THROUGH A FAMILY MEDICINE APPROACH IN THE WORK AREA OF RAJABASA INDAH COMMUNITY HEALTH CENTER - Farida, Lulu; Ernawati, Tutik (CV. Jasa Sukses Abadi, 2025)
Senile cataracts and obesity are two prevalent health conditions frequently observed among the adult and elderly population. Senile cataracts are characterized by lens clouding, leading to visual impairment, while obesity involves excessive fat accumulation, which can exacerbate ocular health through mechanisms of oxidative stress and systemic inflammation. The aim of this study was to apply a holistic and comprehensive family medicine approach to identify both internal and external risk factors and manage these issues based on Evidence-Based Medicine, incorporating family-approached, patient-centered, and community-oriented care. This research was conducted as a case report, with primary data gathered through anamnesis, physical examination, and home visits, and secondary data collected from the patient’s medical records. The case involved a 48-year-old male, Mr. D, who presented with progressively worsening blurred vision in his right eye over the past five months, originating two years prior. The patient reported overeating habits without regular physical activity. Physical examination revealed stable vital signs and a BMI of 36.3 kg/m² (obesity grade II). Local eye exam findings showed a right eye visual acuity of 1/300 with lens opacity and a negative shadow test. Both the patient and his family expressed concern due to their limited understanding of his condition. The diagnosis and management were carried out holistically—emphasizing patient-centered care, family involvement, and community support—based on current theories and research. Post-intervention, there was a notable improvement in the patient’s and family’s knowledge and behavior, contributing to better quality of life and overall health maintenance.